The Impact of Fintech Enterprises on the Level of Competition in the Financial Sector. Increase or Decrease in Competition? - Pawłowska, Małgorzata (Journal of Finance and Financial Law, 2023)
The purpose of the article. The aim of this paper is to examine the impact of digital technologies, including FinTechs, on competition in the EU banking sector. Methodology. This paper consists of qualitative and quantitative analysis using panel regression models. In the theoretical part, on the basis of the available literature on the subject, the important role of FinTech enterprises in shaping the level of competitiveness in the financial sector, all over the world, including in the EU, was demonstrated. The analysis takes into account the impact of FinTechs, m.in. on barriers to entry and price discrimination. BigTech companies are also included in the theoretical part. Finally, the SCP model was used in the quantitative study. The quantitative study was conducted using linear regressions on panel data for the years 2010–2020. Results of the research. Despite the ambiguous impact of digital techniques on banks’ profitability, the results showed that the increasing size of the banking sector did not result in an increase in profitability due to other market players. In addition, the ongoing consolidation has not resulted in a decrease in competition in the EU banking market, due to FinTech solutions. In addition, the qualitative analysis showed that FinTechs have changed the conditions of competition in the financial market.